Heat Safety in the Workplace: Modified Delphi Consensus to Establish Strategies and Resources to Protect the US Workers. (26th August 2021) - Morrissey, Margaret C.; Casa, Douglas J.; Brewer, Gabrielle J.; Adams, William M.; Hosokawa, Yuri; Benjamin, Courteney L.; Grundstein, Andrew J.; Hostler, David; McDermott, Brendon P.; McQuerry, Meredith L.; Stearns, Rebecca L.; Filep, Erica M.; et al.
Abstract: The purpose of this consensus document was to develop feasible, evidence‐based occupational heat safety recommendations to protect the US workers that experience heat stress. Heat safety recommendations were created to protect worker health and to avoid productivity losses associated with occupational heat stress. Recommendations were tailored to be utilized by safety managers, industrial hygienists, and the employers who bear responsibility for implementing heat safety plans. An interdisciplinary roundtable comprised of 51 experts was assembled to create a narrative review summarizing current data and gaps in knowledge within eight heat safety topics: (a) heat hygiene, (b) hydration, (c) heat acclimatization, (d) environmental monitoring, (e) physiological monitoring, (f) body cooling, (g) textiles and personal protective gear, and (h) emergency action plan implementation. The consensus‐based recommendations for each topic were created using the Delphi method and evaluated based on scientific evidence, feasibility, and clarity. The current document presents 40 occupational heat safety recommendations across all eight topics. Establishing these recommendations will help organizations and employers create effective heat safety plans for their workplaces, address factors that limit the implementation of heat safety best‐practices and protect worker health and productivity. Plain Language Summary: Workers who experience heat stress on the job are at greater risk for heat‐related injuries, illnesses, and productivity losses. This document was created to present effective heat safety recommendations to protect workers from the dangers of heat. A meeting of 51 experts created 40 heat safety recommendations within eight heat safety topics: heat hygiene, hydration, heat acclimatization, environmental monitoring, physiological monitoring, body cooling, textiles and personal protective gear, and emergency action plan implementation. These recommendations will assist safety managers and employers implement heat safety recommendations that can be implemented at their worksite and can protect their workers. Key Points: This document presents feasible, evidenced‐based occupational heat safety recommendations to protect workers from the dangers of heat A roundtable of 51 experts created 40 heat safety recommendations within eight heat safety topics: heat hygiene, hydration, heat acclimatization, environmental monitoring, physiological monitoring, body cooling, textiles and personal protective gear, and emergency action plan implementation Implementing feasible and effective heat safety plans in the workplace will protect worker health and mitigate productivity losses